Harmonic spectra of BLDC motor supplied by a solar PV multilevel inverter - Afaneen Anwer Abbood (Institute of Advanced Engineering and Science, 2020)
The multilevel inverters have been used especially in renewable energy aspects in order to assess total harmonic distortion (THD). THD is considered to produce a good quality of current signal of BLDC motor drive. In this paper, a solar PV inveter fed brushless DC (BLDC) motor drive is discussed considering two topologies of three phase multilevel inverters. These topologies are flying capacitor and clamped diode inverters. The inverter efficiency and output power have an effectiveness on THD values. A boost dc to dc converter using incremental conductance maximum power point tracking (INC-MPPT) is implemented with a solar PV. The mathematical model of the proposed systems ares tudied via simulation using Matlab/Simulink. The simulation results of a BLDC motor based on two multilevel inverters are compared with each other considering the THD and the utilization of the dc-bus voltage, the comparition verified that the clamped diode inverter has a better harmonic spectra.still the overshoot is a little bit high in the two types of inverter that are proposed.